ROLE OF INITIAL AND ENTREPRENEURIAL STUDENTS IN ENTERPRENEURING LIFE IMPROVEMENT IN CLASS X STUDENTS IN SMA ISLAM AL-AZHAR PONTIANAK - RIZKA AMANDA (J-MD Jurnal Manajemen Dakwah, 2021)
The problem raised here is how the techniques for developing craftsmanship and entrepreneurship through craft and entrepreneurship subjects for class X students at Al-Azhar Islamic High School in Pontianak, what is the role of craft and entrepreneurship subjects in developing the craft and entrepreneurial spirit of class X students in SMA Islam Al-Azhar Pontianak, and what obstacles are encountered in developing the spirit of craftsmanship and entrepreneurship through craft and entrepreneurship subjects for class X students at SMA Islam Al-Azhar Pontianak. Techniques for developing craftsmanship and entrepreneurship through craft and entrepreneurship subjects for class X students at SMA Islam Al-Azhar Pontianak, are carried out by providing theory, practice, and mentoring. In addition, it is supported by the attitude of residents of X SMA Islam Al-Azhar Pontianak who support, supporting facilities and infrastructure, revolving fund loans from the Islamic High School Al-Azhar Pontianak, and cooperation with various parties. The role of craft and entrepreneurship subjects in the development of the craftsmanship and entrepreneurial spirit of class X students at Al-Azhar Islamic High School in Pontianak are: (a) Developing the craftsmanship and entrepreneurial spirit of class X students in the form of creative and innovative personalities, in which grade X students have a full attitude confident, have initiative, have achievement motives, have a leadership spirit and dare to take risks. (b) Play a role in increasing the independence of class X students. Grade X students have the skills to be self-employed as independent, learn to have responsibility, and be more independent in fulfilling their daily needs. (c) Forming a mental attitude of class X students who never give up, if grade X students experience obstacles or failures from the business they have set up, students do not easily give up but try to find a way out.